The Influence of Competence, Training, and Efficacy on the Development Expectations of Widyaiswara with Affective Commitment as a Moderating Variable in Agencies Implementing Talent Management - Siti Tunsiah; Mahendro Sumardjo; Faisal Marzuki (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research explores how competence, training, and self-efficacy influence the growth expectations of widyaiswara, with affective commitment serving as a moderating variable in institutions that have adopted talent management practices. Data were collected via Google Forms containing statements related to each of the studied variables. The sample consisted of 100 widyaiswara respondents. Data analysis was conducted using SmartPLS 4.0, employing the PLS method for hypothesis testing, which involved two stages: evaluation of the outer model and the inner model. The findings indicate that competence does not have a significant effect on growth expectations. In contrast, both training and self-efficacy show a significant positive impact. Additionally, the moderating role of affective commitment does not influence the relationship between competence and growth expectations, but it significantly strengthens the effect of training on growth expectations.